2017
DOI: 10.1051/matecconf/201710103014
|View full text |Cite
|
Sign up to set email alerts
|

Influences of pitch-length louvered strip insert on thermal characteristic in concentric pipe heat exchanger

Abstract: Abstract. The effects of pitch-length louvered strip inserts with a forward arrangement on heat transfer and friction factor characteristics in a concentric pipe heat exchanger were experimentally investigated. Louvered strip insert was installed inside the tube. For comparison, the experiment without louvered strip (plain tube) was conducted. All cases were tested under steady state condition for Reynolds number ranging from 5300-17,500. The results show that the utilization of louvered strip insert produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…Re, and therefore also the convective heat transfer, improved accordingly. These results are in coherence with previously conducted studies [13][14][15]. Figure 5 also shows that, for backward louvered strip inserts, a pitch S of 40 mm provided the highest Nu and was followed by those of 50 and 60 mm.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Re, and therefore also the convective heat transfer, improved accordingly. These results are in coherence with previously conducted studies [13][14][15]. Figure 5 also shows that, for backward louvered strip inserts, a pitch S of 40 mm provided the highest Nu and was followed by those of 50 and 60 mm.…”
Section: Resultssupporting
confidence: 91%
“…Moreover, as represented in Figures 5 and 10, the present calculation provides the correlation of the Nu and f to Re, respectively. The tendency is considered consistent with the experimental results from previous works [13][14][15]. It is reasonable that the backward louvered strip inserts can give a higher friction factor compared to the forward design [14] because the fluid flow is directly blocked by the louvered strip inserts with the backward arrangement.…”
Section: Conflicts Of Interestsupporting
confidence: 90%
See 1 more Smart Citation
“…Nowadays, the most commonly used turbulators are twisted tapes (TTs), [2][3][4][5][6][7] swirl generating curved conical turbulators, 8 wire coils (WCs), [9][10][11][12][13][14][15][16][17][18][19][20] perforated inserts, [2][3][4][5][6][7][21][22][23][24] and so forth. Out of so many different shapes and sized inserts, the louvered strips (LS) 21,22,[25][26][27][28][29][30][31] turbulator is one of them. LS looks like ellipticalshaped leaves that are mounted on a small diameter core rod.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum positive result was seen with θ=25°, the corresponding increase in heat transfer ratio was between 1.03 and 1.12. Yaningsih and Wijayanta 30 have experimented with deducing the effect of different pitches of LS on thermohydraulic properties inside a tube. It has been observed that Nu and f both increase as pitch values of LS decreased, and maximum enhancement of 1.12 in heat transfer was reported for 40 mm pitched LS insert.…”
Section: Introductionmentioning
confidence: 99%